Molecular characterisation of Bartonella species in cats from Sao Luis, state of Maranhao, north-eastern Brazil - Costa de Oliveira Braga, Maria do Socorro [UNESP]; Vissotto de Paiva Diniz, Pedro Paulo; Andre, Marcos Rogerio [UNESP]; de Bortoli, Caroline Placidi [UNESP]; Machado, Rosangela Zacarias [UNESP] (Fundacão Oswaldo Cruz, 2012)
Bartonella species are fastidious bacteria that predominantly infect mammalian erythrocytes and endothelial cells and cause long-lasting bacteraemia in their reservoir hosts. Reports that describe the epidemiology of bartonellosis in Brazil are limited. This study aimed to detect and characterise Bartonella spp DNA from cat blood samples in Sao Luis, Maranhao, north-eastern Brazil. Among 200 cats tested for multiple genes, nine (4.5%) were positive for Bartonella spp: six cats for Bartonella henselae and three for Bartonella clarridgeiae. Based on the phylogenetic analysis of four genes, the B. henselae strain matched strains previously observed in Brazil and was positioned in the same clade as B. henselae isolates from the United States of America. Moreover, sequence alignment demonstrated that the B. clarridgeiae strain detected in the present study was the same as the one recently detected in cats from southern Brazil.
Keywords: Bartonella henselae; Bartonella clarridgeiae; Cat; north-eastern Brazil